Identifikasi Potensi Jeruk Purut Sebagai Demulsifier Untuk Memisahkan Air Dari Emulsi Minyak di Lapangan Minyak Riau - Tomi Erfando (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Emulsion stability is an indicator that needs to be controlled to prevent the degradation of petroleum quality. Emulsion breakdown is one of the mechanisms to separate the water phase from oil. It is transformed into a chemical compound that is expected to function as emulsion blocking or commonly known as a demulsifier. An organic demulsifier is one of the right ideas in preventing environmental pollution without diminishing its main function as an emulsion breaker. The bottle test method is one of the most commonly used methods in demulsification tests. Testing using this method is done by inserting the prepared emulsion into the bottle, then it will be placed into a waterbath under certain temperature conditions for several hours. This test will be done by looking at the demulsification that occurs every 30 minutes. From the testing of temperature, concentration, and effectiveness of the formulated formula, an optimal condition is obtained based on the highest demulsification efficiency. Based on the research, optimal condition of organic demulsifier formula is (3ml, 80˚C) with 7 ml demulsification efficiency. The results obtained from organic material formulations have not been able to increase the effectiveness of emulsion-breaking processes compared to commercial demulsifiers and basecase conditions (20 ml).